ÜBER FREMDSPRACHENLERNEN DISKUTIEREN – MIT HILFE DIALOGISCHER LERNTAGEBÜCHER - Nerlicki, Krzysztof (Neofilolog, 2020)
Learning journals are widely used in second/foreign language research. They are not only tools to gather data but also contribute to optimization of the learning process and help students become more autonomous. The discussion presented here focuses on dialogue journals, which are used for ongoing written interaction between the teacher and learners. The paper provides a terminological basis, gives examples of topics and describes the characteristics of the teacher-student dialogue management. The advantages and disadvantages of dialogue journals are discussed from the didactic perspective. The last part of the paper concerns empirical problems to be taken into account when learning journals are introduced and used.